2019
DOI: 10.1175/mwr-d-18-0379.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Exploration of Diurnal Oscillations in Tropical Cyclones

Abstract: Diurnal oscillations of infrared cloud-top brightness temperatures (Tbs) in tropical cyclones (TCs) as inferred from storm-centered, direction-relative longwave infrared (~11 μm) imagery are quantified for Northern Hemisphere TCs (2005–15) using statistical methods. These methods show that 45%, 54%, and 61% of at least tropical storm-, hurricane-, and major hurricane-strength TC cases have moderate or strong diurnal signals. Principal component analysis–based average behavior of all TCs with intensities of 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…During the compositing time period, since satellites on the A-Train flew a sun-synchronous orbit with equator local crossing times of 0130 and 1330 (Stephens et al 2002), the A-Train products are biased toward the local time of observation. However, we do not expect this to be problematic for the interpretation of our results since the diurnal cycle of convection is a relatively small source of variability in the distribution of convection in TCs when compared to sources of variability such as TC size, intensity, and convective asymmetries (Knaff et al 2015(Knaff et al , 2019. Additionally, the local equator crossing times for the A-Train reasonably sample the convective extrema, both in terms of area covered and heights reached (Liu and Zipser 2008).…”
Section: Compositing Philosophy and Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…During the compositing time period, since satellites on the A-Train flew a sun-synchronous orbit with equator local crossing times of 0130 and 1330 (Stephens et al 2002), the A-Train products are biased toward the local time of observation. However, we do not expect this to be problematic for the interpretation of our results since the diurnal cycle of convection is a relatively small source of variability in the distribution of convection in TCs when compared to sources of variability such as TC size, intensity, and convective asymmetries (Knaff et al 2015(Knaff et al , 2019. Additionally, the local equator crossing times for the A-Train reasonably sample the convective extrema, both in terms of area covered and heights reached (Liu and Zipser 2008).…”
Section: Compositing Philosophy and Methodsmentioning
confidence: 75%
“…Data are collected in the vicinity of intensifying TCs based on best track locations and intensities from the Automated Tropical Cyclone Forecasting system (ATCF; Sampson and Schrader 2000). Best track uncertainty estimates are typically 15-40 nautical miles (28-74 km) in terms of location and 8-12 kt (4-6 m s 21 ) in terms of intensity (Knaff et al 2010;Torn and Snyder 2012). These uncertainties are small for the purpose of compositing at large distances from the TC center.…”
Section: Compositing Philosophy and Methodsmentioning
confidence: 99%
“…It is therefore essential that we are able to accurately forecast TC rainfall both in terms of timing and intensity. A number of observational studies have already found a clear diurnal cycle in the coverage and maximum height of canopy clouds around TCs (Browner et al, ; Dunion et al, ; Knaff et al, ; Kossin, ; Lajoie & Butterworth, ; Leppert & Cecil, ; Muramatsu, ; Steranka et al, ; Wu & Ruan, ). The diurnal cycle is one potentially predictable and important component of TC precipitation variability.…”
Section: Introductionmentioning
confidence: 99%
“…The IBTrACS data does not capture this oscillation, probably due to the limited time sampling. This may be a manifestation of the diurnal radiation cycle as noted by Tang & Zhang 42 , Dunion et al 43,44 and Knaff et al 45 , amongst others. From simulation studies, Tang & Zhang 42 in particular note that the absence of a diurnal cycle (principally night time cooling) fails to trigger convection outside the cyclone inner core.…”
Section: Dataset Datamentioning
confidence: 67%
“… 43 , 44 and Knaff et al . 45 , amongst others. From simulation studies, Tang & Zhang 42 in particular note that the absence of a diurnal cycle (principally night time cooling) fails to trigger convection outside the cyclone inner core.…”
Section: Technical Validationmentioning
confidence: 98%